Modern optimization and simulation methods in managerial and business economics: A review - Laura Calvet; Rocio de la Torre; Anita Goyal; Mage Marmol; Angel A. Juan (Administrative Sciences, 2020)
Managerial and Business Economics (ME/BE) aims at using quantitative and computational methods to make an efficient (ideally optimal) assignment of the scarce resources owned by firms and organizations. In the current global market, characterized by a fierce competition, an optimal use of the available resources is more important than ever for guaranteeing the economical sustainability of organizations and enterprises of any size. Heuristic optimization algorithms and simulation methods have been successfully employed to analyze and enhance complex systems and processes in a myriad of ME/BE-related fields. This paper reviews recent works on the use of these methodologies in competitive markets, as well as in imperfect markets considering externalities. The paper also discusses open challenges and how state-of-the art methods combining optimization, simulation, and machine learning can contribute to properly address them.
Keywords: 350; heuristic optimization; managerial/business economics; microeconomics; simulation